2013
DOI: 10.1007/s12663-013-0483-x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Clinical Trial Comparing 3D and Standard Miniplates in Treatment of Mandibular Symphysis and Parasymphysis Fractures

Abstract: The use of 3D miniplates for symphysis and parasymphysis fracture fixation was efficacious enough to bear the masticatory load during osteosynthesis of the fracture. Although 3D miniplate system is difficult to adapt and difficult to use in cases of fractures involving the mental nerve, they provide the advantage of less operative time and less implant material in treatment of symphysis and parasymphysis fracture, with clinical results almost similar to those seen with conventional miniplate osteosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 12 publications
10
22
0
Order By: Relevance
“…In this study, none of the patients in either of the groups had nonunion, plate fracture, or loosening of plate and screws within the follow up period and this is in agreement with Agrawal et al (27) who reported that no such significant complications were noted in both conventional and 3D miniplates. Also Melek et al (36) reported that in their study of 3D plate in mandibular angle fracture.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, none of the patients in either of the groups had nonunion, plate fracture, or loosening of plate and screws within the follow up period and this is in agreement with Agrawal et al (27) who reported that no such significant complications were noted in both conventional and 3D miniplates. Also Melek et al (36) reported that in their study of 3D plate in mandibular angle fracture.…”
Section: Discussionsupporting
confidence: 93%
“…The time taken from the 3D plate adaptation to the definitive fixation in this study ranged from 5 to 10 min. It had a faster fixation time compared to the conventional miniplates which had a range of 10-15 min fixation time and this is in agreement with Agrawal et al (27) who reported that the operative time with 3D plates in the treatment of symphysis and parasymphysis fractures is lesser than conventional miniplates. They suggested that the operative time is shorter because of the simultaneous stabilization at both superior and inferior borders and less implant material is used in symphysis and parasymphysis region.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The goal must be accomplished by means that will produce the least disability, risk and shortest recovery period for the patient. 11 The treatment of mandibular fractures has evolved over a period of time from old methods of bandaging and splinting, which are forms of closed reduction, to the more recent methods of open reduction. 1 General acceptance of open osteosynthesis did not appear in maxillofacial literature, until an organized research was done by the AO group in 1950.…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular fractures are frequent in facial trauma. With the increase in facial trauma in incidence due to automobile‐ and industrial‐related accidents, the treatment of mandibular fractures has become important for the maxillofacial surgeon [1]. During past decades, various types of techniques have been developed to provide stable fixation for mandibular fractures and osteotomies.…”
Section: Introductionmentioning
confidence: 99%